Kontra altapresyon kapuso kag kapamilya iririmaw ta! - Bernabe, John Marvin S., et. al; Biaoco, Beverly G.
Hypertension is one of the leading causes of mortality worldwide. According to the World Health Organization, it causes 13% of global fatalities resulting to 5,000,000 premature deaths each year.